2018
DOI: 10.1097/iae.0000000000001686
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Analysis of Submacular Perforating Scleral Vessels by Enhanced Depth Imaging Optical Coherence Tomography

Abstract: Purpose: To analyze submacular perforating scleral vessels (PSVs) using enhanced depth imaging spectral domain optical coherence tomography (EDI-SDOCT). Methods: Twenty-two eyes of 11 healthy women were included in this retrospective study. Central EDI-SDOCT scans (3 × 4.5 × 1.9 mm, 13.5 mm2 scan area) were acquired and postprocessed by denoising, manual sclera segmentation, and PSV investigated by five graders. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“… 23 The users' view is therefore restricted along an axis and is “framed.” Recent techniques of 3D OCT rendering add a new dimension to OCT interpretation, disclosing important spatial relationships within the neurosensory retina and choroid. 24 28 …”
Section: Discussionmentioning
confidence: 99%
“… 23 The users' view is therefore restricted along an axis and is “framed.” Recent techniques of 3D OCT rendering add a new dimension to OCT interpretation, disclosing important spatial relationships within the neurosensory retina and choroid. 24 28 …”
Section: Discussionmentioning
confidence: 99%
“…However, the sample size of the study was quite small (41 eyes from 39 patients), and the scanning area was not specifically defined. The study by Rothenbuehler et al ( 17 ) counted PSV in 22 emmetropic eyes based on 3D imaging and found the PSV for the central 1 mm diameter and 3 mm diameter to be 0.2 ± 0.5 (range 0–2) and 2.1 ± 1.8 (range 0–7), respectively, which is consistent with our data on highly myopic eyes without MM (0.29 ± 0.49 for central 1 mm diameter, 1.93 ± 1.27 central 3 mm diameter). In contrast, our study described PSV distribution better, using a larger scanning scope (9 mm diameter), and revealed the predictive effect of PSV on MM based on ATN staging.…”
Section: Discussionmentioning
confidence: 99%
“…Rothenbuehler et al could image the perforating scleral vessels but in a very short field (4.5 mm centered in the macula) using EDI. 9 With SS-OCT, we could perform images with wilder fields and deeper visualization.…”
Section: Discussionmentioning
confidence: 99%
“…6 There have been previous reports showing perforating vessels using OCT in myopes. 7,8 However, previous reports analyzed spectral domain OCT over a smaller area 9 .…”
Section: Introductionmentioning
confidence: 99%